Penerapan Augmented Reality sebagai Alat Pemasaran untuk Meningkatkan Keterlibatan dan Loyalitas Konsumen: Studi pada Aplikasi IKEA Place - Angelina Cindy Setiawan; Amelia Setiawan; Hamfri Djajadikerta (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2025)
Augmented Reality (AR) technology has emerged as an innovative tool in digital marketing, particularly in enhancing consumer engagement and brand loyalty. This study explores how AR implementation in IKEA Place contributes to a more interactive and personalized shopping experience. AR allows consumers to visualize furniture in their real environment, increasing confidence in purchasing decisions and reducing product return rates. Using a literature review approach, this research identifies the benefits of AR in fostering emotional connections between consumers and brands, while also highlighting challenges such as visual accuracy, consumer readiness, digital integration, and infrastructure limitations. Findings suggest that AR not only enhances consumer engagement but also serves as a differentiation strategy that strengthens brand loyalty. To maximize AR’s potential, IKEA should improve product visualization accuracy, expand consumer education, and ensure broader accessibility to AR technology. Ultimately, AR can become a key component in modern marketing strategies, driving both consumer attraction and long-term retention.